Factors influencing perceptions of local community on 'kelulut' honey as agrotourism product - Kunasekaran, Puvaneswaran; Nizartul Fuza; Engku Hassan, Engku Nor Kamilah; Ramachandran, Sridar (Universiti Malaysia Sarawak, 2018)
The purpose of this study was to access local communities’ perception on ‘kelulut’ bee as an agro tourism product. This paper presents the findings of factors affecting local communities’ perception on ‘kelulut’ bee as an agro tourism product in Kampung Sungai Buah, Dengkil, Selangor. Attributes from past studies on impacts of agro tourism to local communities and their attitudes towards agro tourism in general were combined with the research on ‘kelulut’ or stingless bee honey industry. Factor analysis was used as tool in the reduction method. As the result, 41 attributes were identified to have significant contributions to this study and all these attributes were extracted into 13 different groups. Multiple regression analysis was employed to determine which factors were significant to depict local communities’ perception on ‘kelulut’ bee as an agro tourism product and through findings, there were 6 factors found. This study can be used in evaluating local communities’ perception on other new, potentially booming agro tourism products. The findings from this study would also be beneficial to conduct further studies in this area.